THE ANALYZE OF STUDENTS’ PERCEPTIONS OF BLENDED LEARNING AND PHYSICS ACHIEVEMENTS ON PHYSICS UNDERGRADUATE PROGRAM - Rizki Khairida Sinaga; Motlan Motlan (UNIVERSITAS NEGERI MEDAN, 2022)
This study aims to determine students’ perceptions of blended learning in physics in blended learning process and ease of use aspects. This study also consist the correlation with students’ achievements in physics. This research type is correlation research by using online survey aided by google form. The study population was all students of Physics Department consisting of 175 students from 2019 classes. The research sample was taken by random sampling technique consisting of 92 students. This research instrument uses questionnaire contained 17 statements using likert scale 1 – 5 to measures students’ perceptions based on and the students’ achievements in physics get from final marks in Daftar Peserta dan Nilai AKhir (DPNA) of Basics Physics course. Analysis data technique to test the hypothesis used product moment correlation. The results of data analysis obtained that students’ perceptions are high category in blended learning process aspects and very high category in ease of use aspects. Students’ perceptions of blended learning in physics and students’ achievements in physics have positive and moderate correlation with the coefficient of correlation is 0.413. It means that the better design and application of blended learning in physics learning, the better the students' physics learning outcomes will be.